Alien deep [videorecording (DVD)] - Ballard, Robert D. ([Distributed by] Gaiam/Vivendi Entertainment, 2012)
A five-part series on deep sea exploration from the people at National Geographic. Using cutting-edge tools and technologies, Dr. Bob Ballard, discoverer of the Titanic, travels to the most remote parts of the world's oceans, revealing new species, natural wonders and archeological finds.